A Review on Various Medical Image Preprocessing Methods - K. Ojha, K; Khurana, A (International Journal of Computer Sciences and Engineering, 2025)
The appearance of computer aided technologies image handling procedures have turned out to be progressively essential in a wide assortment of restorative applications. Mediation between the insurance of helpful indicative data and noise concealment must be cherished in therapeutic images. Image de-noising is an appropriate issue found in differing image handling and computer vision issues. There are different existing techniques to denoise images. The imperative property of a decent image de-noising model is that it ought to totally evacuate noise beyond what many would consider possible just as save edges. This paper shows a survey of some real work in region of image de-noising. The target in all control is to extricate data about the scene being imaged. The quick advancement in automated therapeutic image recreation and the related improvements in investigation strategies and computer helped determination has supported medicinal imaging into a standout amongst the most vital sub-fields in logical imaging Ultrasound, MRI, CT-Scan are the restorative procedures basically utilized by the radiologist for representation of inside structure of the human body with no medical procedure. These give sufficient data about the human delicate tissue, which helps in the finding of human sicknesses.